FROM EDUCATION TO ACTION: ENVIRONMENTAL LITERACY AS A PREDICTOR OF GREEN CONSUMPTION IN URBAN SOCIETIES - Dhea Clara Salshabella; Dewi Kusuma Wardani; Muhammad Sabandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Global consumption poses significant challenges to sustainable development, making education a vital tool for promoting awareness and responsible green consumption. This study explores environmental literacy as a key link between education and sustainable consumption behavior. Employing a quantitative survey of 400 working-age residents in Surakarta experienced in eco-friendly consumption, the research analyzes how environmental literacy influences green consumption outcomes. Grounded in attitudinal theory, it emphasizes that behavior is shaped by attitudes formed through learning, experience, and social interaction. The results confirm that higher environmental literacy significantly encourages green consumption habits. These findings highlight education’s crucial role in shifting public attitudes and consumption patterns, supporting broader sustainability goals. Moreover, the study suggests important directions for Indonesia’s education system, advocating for the integration of environmental education throughout all academic levels to effectively nurture ecological awareness and responsible consumer behavior.